2009
DOI: 10.1016/j.watres.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Survival of surrogate coronaviruses in water

Abstract: The emergence of a previously unknown coronavirus infection, Severe Acute Respiratory Syndrome (SARS), demonstrated that fecally contaminated liquid droplets are a potential vehicle for the spread of a respiratory virus to large numbers of people. To assess potential risks from this pathway, there is a need for surrogates for SARS coronavirus to provide representative data on viral survival in contaminated water. This study evaluated survival of two surrogate coronaviruses, transmissible gastroenteritis (TGEV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
392
1
20

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(433 citation statements)
references
References 23 publications
20
392
1
20
Order By: Relevance
“…After four weeks in almost the same conditions but at 4 °C, there was less than <1 log 10 infectivity decrease for both viruses. The authors concluded that in case of SARS-CoV re-emergence water contaminated with fecal waste should be considered as a potential vehicle of transmission [111]. …”
Section: Hcovs: Enveloped But Not That Fragilementioning
confidence: 99%
“…After four weeks in almost the same conditions but at 4 °C, there was less than <1 log 10 infectivity decrease for both viruses. The authors concluded that in case of SARS-CoV re-emergence water contaminated with fecal waste should be considered as a potential vehicle of transmission [111]. …”
Section: Hcovs: Enveloped But Not That Fragilementioning
confidence: 99%
“…81 Interestingly, not all enveloped viruses rapidly lose their infectivity (Table 3). 85 In two studies of human coronaviruses in water, 77,78 temperature was found to have the most pronounced effect of a range of variables on survivability, with up to an order of magnitude difference in decay rates between samples at 4°C and room temperature. Inactivation rates are highly dependent on the water temperature and matrix.…”
Section: Survival In Municipal Wastewatermentioning
confidence: 99%
“…85 In two studies of human coronaviruses in water, 77,78 temperature was found to have the most pronounced effect of a range of variables on survivability, with up to an order of magnitude difference in decay rates between samples at 4°C and room temperature. 78 Based on the collective data, matrix effects on virus inactivation are complex and vary significantly amongst different viruses and environmental samples. Viruses in sterilized wastewater, for example, are inactivated at different rates than viruses in non-sterilized wastewater.…”
Section: Survival In Municipal Wastewatermentioning
confidence: 99%
“…30 However, a study investigating enveloped surrogates of coronaviruses (transmissible gastroenteritis and mouse hepatitis) demonstrated that these enveloped viruses remained infectious in wastewater for weeks, with 1 to 2 log unit removal after 1 week. 46 Additionally, enveloped Inf luenza viruses have previously been detected in sewage; 47 however, the potential for infection through water exposure remains unknown. These data suggest the potential for both the environmental persistence and transmission of the enveloped Ebola virus.…”
Section: ■ Ebola Virus Survival In the Environmentmentioning
confidence: 99%